A rapid detection of Campylobacter jejuni in chickens by nested polymerase chain reaction - Jiménez, Karim L. (2007)
In order to standardize a rapid method for detecting C. jejuni in chickens, it was taken cloacal swabs from 50 chickens of seven-week lifetime belonging to several markets of Lima's city. DNA was extracted by using organic solvents and the presence of C. jejuni was detected by means of Nested-PCR using specific primers for 16S ribosomal and hipO genes. In parallel with this rapid DNA-based approach, it was isolated C. jejuni by conventional filtration bacteriological methods and selective culture mediums. The rapid and conventional methods used in this study, detected C jejuni in 48/50 (96%) and 29/50 (58%) respectively. These findings indicate than the rapid method has a higher sensitivity lhan the conventional one.